Os encontros de Edgar Allan Poe e Pedro Morelli em Contos do Edgar: uma análise tradutória - Cardoso Filho, Milton José (2019)
This dissertation intends to analyze the television series Contos do Edgar, by Pedro Morelli, a work translated / adapted from six short stories written by Edgar Allan Poe. In the series, Morelli adapted the diegese of the stories, updating them to the scenario of a current São Paulo. The research problem is focused in the questioning: how are the narrative foundations of Edgar Allan Poe – amid Pedro Morelli's constructive translation recomposition for the television work - present in the series Contos do Edgar? To answer this question, it was outlined as a research plan to analyze specifically three narrative elements: the plot, the character and the narrator. This is a case study with a qualitative approach, in which concepts of Gancho's narrative and Gaudreault's and Jost's concepts of mega-narrator were used. The logic of Edgar Morin's complex thinking served to interconnect the concepts of: Julio Plaza, Ana Hutcheon, Aroldo de Campos, Oswald de Andrade and Amálio Pinheiro for appreciation about translation / adaptation. With respect to the narrative elements, the theoretical contributions of Vanoye and Goliot-Lété, Tarkovski, Xavier and other scientists of narratological science were also sought. The results of the research showed that the television series, although it is a free translation / adaptation, has the narrative fundamentals of Edgar Allan Poe, showing that the filmmaker keeps traces of the writings of Poe in his constructive translation recomposition